Access to CF3‐Containing Cyclopentaquinolinone Derivatives from Indolyl‐ynones via Silver‐Catalyzed One‐pot Reaction. Issue 4 (20th December 2018) - Han, Guifang; Xue, Li; Zhao, Lili; Zhu, Tiaozhen; Hou, Jingli; Song, Yuguang; Liu, Yangping
Abstract: An unexpected Ag(I)‐catalyzed cascade reaction between substituted indolyl‐ynone and Togni's reagent has been disclosed in which multiple processes occur including indole dearomatization, ring expansion, trifluoro‐methylation and dehydrogenation. This one‐pot reaction can be used to conveniently access diverse CF3 ‐containing multisubstituted cyclopentaquinolinone scaffolds in moderate to good yields. Abstract :